Technical and tactical preparation of elite athletes in team sports with limited playing space (on the material of volleyball) - Владимир Гамалий; Ольга Шленская (National University of Physical Education and Sport of Ukraine, 2016)
The paper summarizes the new data on the technical and tactical preparation of elite athletes in team sports. The main content of the paper involves the data of own research on the issue of improving sports mastery in elite volleyball players. The formulas and rating scales are developed for assessing the technical and tactical preparedness of team players based on the indicators of their competitive activity (efficiency of attacking actions, the effectiveness of the serving, the effectiveness of the technical and tactical actions in attack). The program of improving technical and tactical actions in attack in elite volleyball players with different team role was proposed based on pedagogical analysis and interpretation of indicators of competitive activity.